Educational Concerns, Health Concerns and Mental Health During Early COVID-19 School Closures: The Role of Perceived Support by Teachers, Family, and Friends - Dändliker, Lena; Brünecke, Isabel; Citterio, Paola; Lochmatter, Fabienne; Buchmann, Marlis; Grütter, Jeanine (Frontiers in Psychology, 2022)
This study investigated whether school closures and health-related uncertainties in the early phases of the COVID-19 pandemic posed risk factors for adolescents’ mental health and whether perceived social support by parents, teachers, and friends functioned as protective factors. In particular, we argued that perceived social support would buffer negative associations between educational and health concerns and mental health. Based on a person-centered approach, we first examined resilience profiles. These profiles reflect configurations regarding the levels of these risk and protective factors and levels of mental health. Second, we analysed whether these risk and protective factors predicted adolescents’ mental health differently by using a variable-centered approach. The sample consisted of 1’562 adolescents (Mage = 16.18, SD = 1.48, range = 14-20 years; 72% females) in lower and higher secondary education from three regions: German-speak¬ing part of Switzerland, N = 486; Italian-speaking part of Switzerland, N = 760; and Northern Italy N = 316. Results from the person-centered approach revealed three latent profiles characterized by low (19%), average (47%), or high resilience (34%). Lower resilience was associated with higher educa-tional concerns, lower perceived social support, and lower mental health, while high resilience was characterized by lower concerns, higher support, and higher mental health. Importantly, educational concerns varied more between profiles than health concerns, and perceived teacher and family support varied more than perceived friend support. Corroborating these findings, the variable-centered approach (i.e., a path analysis) revealed that educational concerns were a stronger predictor than health con¬cerns and pointed to a higher relative importance of perceived family support for adolescents’ men¬tal health relative to perceived teacher and friend support. Taken together, the findings suggest that adolescents’ educational concerns and perceived family support, respectively, were stronger risk and protective factors for their mental health during school closures related to the COVID-19 pandemic. Finally, adolescents from regions being more exposed to the COVID-19 pandemic, namely, Italian-speaking part of Switzerland and Northern Italy, were more likely classified in the low or the average rather than in the high resilience profile compared to students from the region with lower exposure, that is, the German-speaking part of Switzerland.